Analisis penyebab rendahnya motivasi belajar dalam pembelajaran ips peserta didik kelas V sekolah dasar - Suciani Alfiah; Siti Istiyati; Hadi Mulyono (Universitas Sebelas Maret, 2021)
Abstract. Motivation to learn is a psychological factor that is intellectual in nature, fosters enthusiasm and pleasure to learn. Motivation to learn provides direction, enthusiasm and persistence in learning. The level of student motivation to learn is influenced by encouragement that comes from within and from outside the student. This research is qualitative descriptive. This study describes the causes of low learning motivation in social studies learning in class V elementary school. The research subjects were 30 grade V students. However, the data collected was only 22 students. Collecting data using interviews with class V teachers, grade V students, and using questionnaires to class V teachers, grade V students, and class V students' parents. The findings came from intrinsic factors. The reasons are 1) the demand to study social studies with a lot of material; 2) high embarrassment, less interesting learning activities; 3) less absorbing social studies material because students are lazy to repeat reading; 4) complained, felt pressured because IPS material had to be read a lot; 5) learning motivation is low because the teacher's teaching method is less attractive; 6) The teaching method is less attractive due to the lack of teacher references